"A problem shared is a problem solved:" integrating human-centered design and implementation science to optimize lay counselor supervision in Western Kenya - Noah S. Triplett; Anne Mbwayo; Sharon Kiche; Enoch Sackey; Rashed AlRasheed; Daisy Anyango Okoth; Omariba Anne Nyaboke; Cyrilla Amanya; Shannon Dorsey (Elsevier, 2024)
Implementation science and human-centered design (HCD) offer useful frameworks and methods for considering and designing for individuals' needs and preferences when implementing new interventions or technologies in global health. When used in tandem, the two approaches may blend creative and partnered research methods with a focus on the factors necessary to design, implement, and sustain interventions. However, research is needed that describes the process of blending these two approaches and explores the experiences of community partners. This study builds from a stepped-wedge cluster-randomized trial in Western Kenya, wherein teachers and community health volunteers have been trained to provide trauma-focused cognitive behavioral therapy (TF-CBT). Mobile phones emerged as a tool to supervise lay counselors from afar; however, their use was characterized by unique challenges. Informed by human-centered design and implementation science, we first engaged lay counselors (n = 24) and supervisors (n = 3) in individual semi-structured interviews then hosted an in-person participatory workshop to "co-design" solutions to optimize the use of mobile phone supervision. Lay counselors participated in focus group discussions regarding their experiences in the workshop. Focus group transcripts were analyzed using thematic analysis. We describe our approach as well as focus group discussion results. Counselors felt the workshop was a valuable experience to learn new strategies from their colleagues, and they enjoyed the "collaborative spirit" that emerged as they worked together. Counselors felt that varying small and large group discussions fostered participation by creating opportunities for more people to engage and share their thoughts. Counselors suggested the approach be improved by providing more tangible materials (e.g., hand-outs) and more closely following a schedule of activities. It is important to also center stakeholders' experiences as partners in the research process. Though counselors largely expressed positive sentiments, they also shared valuable suggestions for how to improve participatory research practices in the future.